Graduate study for the twenty-first century : how to build an academic career in the humanities - Semenza, Gregory M. Colón, 1972- (Palgrave Macmillan, 2005)
Many graduate students continue to be regarded as 'apprentices' despite the fact that they are expected to design and teach their own classes, serve on university committees, and conference and publish regularly. "The Chronicle of Higher Education" reports that the attrition rate for American Ph. D. programmes is at an all-time high, between 40 per cent and 50 per cent (higher for women and minorities). Of those who finish, only one in three will secure tenure-track jobs. These statistics highlight: waste of millions of dollars by universities and of time and energy by students. Rather than teaching graduate students how to be graduate students, then, the guide prepares them for what they really seek: a successful academic career.